2011
DOI: 10.1111/j.1558-5646.2010.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Population Divergence Linked With Co‐variation Between Coloration and Sexual Display in Strawberry Poison Frogs

Abstract: The likelihood of speciation is assumed to increase when sexually selected traits diverge together with ecologically important traits. According to sexual selection theory, the evolution of exaggerated display behavior is driven by increased mating success, but limited by natural selection, for example, through predation. However, the evolution of aposematic coloration (i.e., an ecologically important trait) could relieve the evolution of exaggerated display behavior from the bound of predation, resulting in j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 84 publications
(139 reference statements)
5
57
0
Order By: Relevance
“…In general, predators learn to avoid aposematic prey more quickly when the diversity of warning signals is low, compared to higher signal diversity (Joron and Mallet 1998;Rowland et al 2007). Geographic differences in warning signals are often thought to be the result of adaptations to local predators (Mallet and Barton 1989;Noonan and Comeault 2009;Chouteau and Angers 2012) or interactions between predation and other selection forces (Rudh et al 2011). The possible explanations for geographic variation in warning signals are similar, regardless of whether the observed warning signal differences are exclusive morphotype regions (i.e., polytypisms) or many morphs co-existing in a single population (i.e., polymorphisms) alongside a dominant morph.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In general, predators learn to avoid aposematic prey more quickly when the diversity of warning signals is low, compared to higher signal diversity (Joron and Mallet 1998;Rowland et al 2007). Geographic differences in warning signals are often thought to be the result of adaptations to local predators (Mallet and Barton 1989;Noonan and Comeault 2009;Chouteau and Angers 2012) or interactions between predation and other selection forces (Rudh et al 2011). The possible explanations for geographic variation in warning signals are similar, regardless of whether the observed warning signal differences are exclusive morphotype regions (i.e., polytypisms) or many morphs co-existing in a single population (i.e., polymorphisms) alongside a dominant morph.…”
Section: Introductionmentioning
confidence: 86%
“…Brown et al (2010) found evidence that divergence in dorsal color within the Bocas del Toro Archipelago was occurring more quickly than would be predicted under a neutral process, such as genetic drift. Underlying factors that might explain the warning signal diversity in the archipelago include sexual selection (Summers et al 1997;Maan and Cummings 2008;Tazzyman and Iwasa 2010;Rudh et al 2011) and predation (Siddiqi et al 2004;Reynolds and Fitzpatrick 2007;Saporito et al 2007b;Maan and Cummings 2008;Brown et al 2010;Wang and Summers 2010;Rudh et al 2011;Maan and Cummings 2012). Previous work has shown that the red morph of O. pumilio in Costa Rica is avoided by predators (Saporito et al 2007b), and that the black spotting pattern on the same morph does not influence the attack rate (Hegna et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a scenario was first suggested for the interspecific diversification of firefly warning signals (Branham & Wenzel 2003), where selection by predators and mate choice are thought to impact the evolution of firefly flashes (Moosman et al 2009). Sexual selection is also thought to play a role in the intra-specific diversification of warning signals in the strawberry poison frog (Oophaga pumilio) (Rudh et al 2011, Cummings & Crothers 2013. Although it is well established that females prefer color morphs that are similar to their own coloration (Summers et al 1999, Maan & Cummings 2008, recent work has shown that predators may not select for local morphs on the basis of color alone (Hegna et al 2013b, Richards-Zawacki et al 2013.…”
Section: Trait Trade-offs and Interactionsmentioning
confidence: 99%
“…Some of the species found to have geographically varying warning signals include Neotropical Heliconius butterflies (Brown & Benson 1974, Brower 1996, Mallet 2010, ladybird beetles (Creed 1966, Brakefield 1985, Dolenská et al 2009, Blount et al 2012, monarch butterflies (Brower 1958, Davis et al 2005, Davis et al 2012, newts (Mochida 2009, Mochida 2011, poison frogs (Daly & Myers 1967, Savage 1968, Summers et al 2003, Wang & Summers 2010, Wang 2011, Rudh et al 2011, Maan & Cummings 2012, Willink et al 2013, RichardsZawacki et al 2013, Hegna et al 2013b), velvet ants (Wilson et al 2012), alpine leaf beetles (Borer et al 2010), and bumble bees (Plowright & Owen 1980). Interestingly, some aposematic species appear to switch between aposematic and cryptic strategies across their distributions.…”
Section: Geographic Variation For Different Preymentioning
confidence: 99%